Dual‐Control Mechanism of Water and Temperature in Automatically Programmable Shape Memory Polymers. Issue 10 (28th July 2022) - Zhang, Jun; Xu, Wanli; Heng, Kejie; Chu, Mingyu; Qian, Binjie; Tang, Junkun; Liu, Zuozhen; Huang, Farong
Abstract: Auto‐programmable shape memory polymers (AP‐SMPs) can deform automatically without external manipulation, exhibiting either a free‐standing temporary shape or a permanent shape. The unique shape memory behaviors derive mainly from control by two factors, water and temperature. However, the control mechanism is unknown. This study analyzes and demonstrates the dual‐control mechanism of water and temperature in the three shape‐changing processes of AP‐SMPs. First, the AP‐SMP is immersed in warm water (50 °C). Asymmetric swelling of bilayer films provides the driving force for the shape auto‐programming of the AP‐SMP. The solvent effect of water reduces the glass transition temperature ( T g ) of the AP‐SMP, which becomes lower than the medium temperature in warm water. AP‐SMP can be programmed automatically. Then, the AP‐SMP is removed from water and placed in air at room temperature. The T g value of the matrix film increases notably in air and exceeds the medium temperature. The temporary shape of the AP‐SMP can thus be fixed. Finally, the AP‐SMP can quickly return to its permanent shape when the medium temperature exceeds the matrix film T g in air. The dual control shape memory mechanism provides insights into the design and development of AP‐SMPs. Abstract : The dual‐control mechanism of water and temperature in automatically programmable shape memory polymers (AP‐SMPs) is studied. Water provides a driving force and controls the T g value of the matrix film. Temperature controls the relationship between the medium temperature and matrix film T g .